Asperger's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The diagnosis of Asperger's Syndrome was made in six children admitted to the psychiatric in-patient Clinic at the Maudsley and Bethlem Royal Hospitals, Denmark Hill, London SE5 8AZ, England.